Goodwin, Baumol & Lewis: How structural change can lead to inequality and stagnation. (25th April 2022) - Rada, Codrina; Schiavone, Ansel; von Arnim, Rudiger
Abstract: This paper presents a labor‐constrained aggregate model of growth that explains stagnation and inequality as the result of structural change, which is defined as an exogenous increase in the employment share of low‐productivity services. Productivity growth is increasing in the labor share, reminiscent of induced technical change. Productivity and real wage growth further are assumed to respond negatively to structural change. We label the positive (negative) difference between these effects dominant Lewis (Baumol) dynamics. In steady state, and across two model variants, structural change leads to stagnation. Only the model version with Keynesian aggregate demand, dominant Lewis dynamics and a weak profit squeeze also exhibits a falling labor share, and hence conforms to key stylized facts.